1997
DOI: 10.1029/96jb02656
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of northern Baffin Bay: Seismic refraction results and tectonic implications

Abstract: Abstract. Two detailed seismic refraction lines were shot in northern Baffin Bay in order to determine the crustal structure and so provide constraints on the complex geological and tectonic history of the area. An array of air guns provided the seismic source, with a total of 16 ocean bottom seismometers as receivers. The data were analyzed by iterative forward modeling of travel times and arrival amplitudes, and the crustal velocity structure obtained was interpreted in the light of previous seismic reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…A review by Balkwill et al (1990) discussed the debate on the development of Baffin Bay: one group suggests that the region formed by seafloor spreading, and another that continental crust is present. Available refraction profiles are consistent with oceanic crust in northern Baffin Bay (Jackson et al, 1979;Reid and Jackson, 1997). In addition, interpretations of the industry reflection lines from 70 to 758N by Jackson et al (1992) indicated the position of the continent-ocean boundary (COB).…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 65%
See 1 more Smart Citation
“…A review by Balkwill et al (1990) discussed the debate on the development of Baffin Bay: one group suggests that the region formed by seafloor spreading, and another that continental crust is present. Available refraction profiles are consistent with oceanic crust in northern Baffin Bay (Jackson et al, 1979;Reid and Jackson, 1997). In addition, interpretations of the industry reflection lines from 70 to 758N by Jackson et al (1992) indicated the position of the continent-ocean boundary (COB).…”
Section: Geological and Geophysical Backgroundmentioning
confidence: 65%
“…There is no evidence for SDRs or a linear magnetic anomaly associated with the slope. A seismic refraction survey across the margin and into Baffin Bay at 728N did not detect high-velocity lower crust (Jackson et al, 1979) and another survey further north in Baffin Bay detected velocities typical of serpentenized lower crust and mantle (Reid and Jackson, 1997). These observations indicate extension with limited volcanism.…”
Section: Interpretation Of the Volcanic Or Non-volcanic Marginmentioning
confidence: 77%
“…Gravity modeling has been a common exercise in studies of deep-crustal structure [e.g., Holbrook et al, 1994b;Horsefield et al, 1994;Chian et al, 1995;Barton and White, 1997a;Lizarralde and Holbrook, 1997;Reid and Jackson, 1997;Mjelde et al, 1998];…”
Section: Discussionmentioning
confidence: 99%
“…1) was defined to encompass all potential oil and gas reservoirs that could be within the 8-to 14-km-thick wedge of Paleogene and Neogene strata that occupies Baffin Bay Basin. The crust underlying Baffin Bay Basin, which formed between magnetic isochron 24 to 13, or 58 to 33 Ma (Saalmann and others, 2005), is variously thought to be oceanic crust formed in a spreading center, crust that reflects upwelling of mafic mantle material (Reid and Jackson, 1997), or extremely attenuated continental crust. The Baffin Bay Basin AU is bounded on the north by the Eurekan Structures AU, to the east and south partly by the Northwest Greenland Rifted Margin and Greater Ungava Fault Zone AUs, and to the west by the Northeastern Canada Rifted Margin AU.…”
Section: Baffin Bay Basin Aumentioning
confidence: 99%